Wise or unwise decision? : Students' and teachers' evaluation of 'step by wicked step' as a literature text in the ESL classroom / Mohamad Irwan Sagir - Sagir, Mohamad Irwan (2013)
In 2010, the Malaysian Ministry of Education has decided to renew the entire content of the literature component in English subject. One of the selections of the newly prescribed literary text is the novel entitled 'Step by Wicked Step' written by Anne Fine. This novel becomes the highlight of this study due to the students' and teachers' negative perceptions of the previous novel selection as claimed by Nurul Atiqah (2003), Vethamani (2003) and Norliana et al. (2009).Therefore, one of the objectives of this study is to identify the variables that significantly influenced students' attitudes towards the novel 'Step by Wicked Step'. Furthermore, the study also attempted to obtain the ESL students' and teachers' evaluation of this particular novel in two different dimensions. The first dimension is to identify the quality or qualities of this novel which makes it appropriate for young adult readers. The second dimension is to identify the strengths and weaknesses of this novel as ESL students' reading materials. In addition, the students' and teachers' suggestions for the improvement of the current literature text selection were also elicited through this study. In order to fulfill these objectives, two research instruments namely questionnaire and semi-structured interview were utilized. The findings of Chi-square correlation analysis revealed that the students' attitudes towards English reading material is the most significant variable that influenced the students' attitude towards reading the novel 'Step bywicked Step'. From the analysis of the respondents' evaluations, it was found that the novel possesses seven from ten qualities of an appropriate young adult's novel as suggested in Paul Zindel's guideline. The analysis of the mean value of the respondents' evaluation also found that the novel has five strong qualities and three weaknesses as an ESL learners reading material.